Evaluation of Wanggu Watershed Carrying Capacity on Water System Indicators in Southeast Sulawesi, Indonesia - Kahirun; Sudia, La Baco; Gandri, La (Indonesian Journal of Environmental Management and Sustainability, 2023)
The water system or hydrological indicators determine the good and bad of a watershed’s carrying capacity. The hydrological indicators include discharge fluctuations, annual flow coefficient, sediment load, flood frequency, and water use index. The purpose of this study was to evaluate the carrying capacity of the Wanggu watershed based on hydrological indicators. The method used is the score and weight method for all hydrological indicator data in accordance with the watershed evaluation guidelines for hydrological indicators. The research data is sourced from primary data and secondary data. Primary data comes from direct observation, while secondary data comes from agencies related to this research. Data analysis using Microsoft Excel in monthly and annual data analysis by producing tables and figures. The results of this study indicate that fluctuations in discharge or the regime coefficient of the Wanggu River Basin are 96.45 which are classified as high, as well as erosion and surface runoff, namely sediment load conditions of 19.73 which are also included in the high category. While the value of the annual flow coefficient is 0.32, the average frequency of flooding every year occurs once in two years and the water use index is 0.69. The three parameters are categorized as being in the middle class. From the accumulated weights and scores of all water system indicator parameters, a value of 111.25 is included in the bad class category. So the Wanggu watershed has a poor carrying capacity value from the water management indicator.